Bisphenol A: An endocrine and metabolic disruptor - Fenichel, Patrick; Chevalier, Nicolas; Brucker-Davis, Françoise (Annales d'endocrinologie, 2013)
Bisphenol A (BPA), initially designed, like diethylstilbestrol, as a synthetic estrogen, has been rapidly and widely used for its cross-linking properties in the manufacture of polycarbonate plastics and epoxy resins. Because of incomplete polymerization and degradation of the polymers by exposure to higher than usual temperatures, BPA leaches out from food and beverage containers, as well as from dental sealants. In humans, free active unconjugated BPA is metabolized by rapid glucurono- or sulfo-conjugation and eliminated via renal clearance. However, exposure to environmental nanomolar concentrations of BPA is ubiquitous and continuous via different routes: oral, air, skin. In rodents, fetal and perinatal exposure to such environmentally relevant doses of BPA has been shown to affect the brain, liver, gut, adipose tissue, endocrine pancreas, mammary gland and reproductive tract and function. Similar concentrations are also able in vitro to impact human malignant breast, prostate, male germ or adipocyte cell lines (with a promoting effect and by interfering with chemotherapy drugs), or to stimulate pancreatic β cell insulin secretion. High levels of BPA have recently been correlated with obesity, diabetes, cardiovascular diseases, polycystic ovarian disease or low sperm count. However, before the real impact of BPA on human health can be clearly assessed, prospective longitudinal epidemiological studies are needed as well as characterization of selective biomarkers to verify long-term exposure and selective imprinting. Le bisphénol A (BPA) est une substance chimique très ubiquitaire présente dans la plupart des plastiques polycarbonés et les résines époxy, qui est relargué sous l’effet de la chaleur et considérée comme présentant un effet de perturbateur endocrinien estrogéno-mimétique. Il est essentiellement absorbé dans l’espèce humaine par voie alimentaire et est retrouvé sous forme libre active dans le sang et sous forme conjuguée dans les urines en vue de son élimination, chez la majorité des individus. La mise en évidence de troubles du développement, de la reproduction, du métabolisme chez les rongeurs exposés à des taux équivalents, pendant des périodes critiques d’exposition fœtale et/ou périnatale, a conduit à s’interroger sur sa responsabilité dans les pathologies humaines correspondantes. D’autant qu’il est capable d’induire in vitro sur des cellules humaines, via des récepteurs membranaires des estrogènes, la prolifération de cellules malignes mammaires ou testiculaires ou d’adipocytes et de réguler la sécrétion insulinique par les îlots β-pancréatiques. Bien que des études épidémiologiques transversales, rétrospectives mettent en évidence une corrélation entre obésité, insulinorésistance, diabète, hypofertilité et les taux de BPA, elles ne permettent pas à elles seules d’attester d’une relation causale et d’évaluer exactement la part de ce potentiel facteur de risque. Seules des études prospectives longitudinales pourraient conforter cette hypothèse ainsi que la caractérisation de biomarqueurs permettant à la fois d’évaluer l’exposition prolongée et continue à de faibles doses de BPA et en même temps de mettre en évidence des modifications moléculaires conduisant à faire la part de l’exposition chronique et de la susceptibilité individuelle.